Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Saintifik pada Materi IPAS Kelas IV SDN 1 Kaliawi Bandar Lampung - Shalshabila, Zahwa; Jaya, Wayan Satria; Lestari, Yulita Dwi (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2025)
The problems in this study are 1) lack of teaching materials in learning science, 2) lack of interest in learning science material, 3) LKPD made and downloaded by teachers from the internet are less interesting, non-contextual images, only summaries of materials and only contain questions and 4) students are less active in learning. Therefore, one effort that can be made is to develop LKPD based on a scientific approach so that students can understand and be interested in the science learning process. The purpose of this study was to determine the level of feasibility and practicality of scientific-based LKPD on science material for grade IV SDN 1 Kaliawi Bandar Lampung. This type of research is research and development that adopts ADDIE (Analysis, Design, Development, Implementation and Evaluation) development. The instruments used are expert validation sheets and student response questionnaire sheets. The results of this research and development state that the feasibility of scientific-based LKPD based on the assessment of material experts obtained a percentage of 92% with very feasible criteria, then language experts gave an assessment with a percentage of 92.73% also with very feasible criteria, while the assessment of media experts obtained a percentage of 89.23% also with very feasible criteria. From the three validation results, it is concluded that the scientific-based LKPD assessment is very feasible and can be applied to grade IV students of SDN 1 Kaliawi Bandar Lampung. While the results of the LKPD assessment on the student response questionnaire as a whole get a very practical category or very feasible to use with a percentage of 87.48%. Based on this explanation, it can be concluded that the development of scientific-based LKPD has very good feasibility and practicality in learning on the material of science for grade IV SDN 1 Kaliawi Bandar Lampung.